Endoscopic band ligation alone and combined with clipping for colonic diverticular bleeding: A retrospective comparative study - Noritaka Ozawa; Kenji Yamazaki; Nae Hasebe; Kazuki Yamauchi; Kaori Koide; Hiroyuki Murase; Saeka Hayashi; Takaaki Hino; Daiki Hirota; Atsushi Soga; Kiichi Otani; Naoya Masuda; et al. (Endoscopy International Open)
Abstract Clipping alone or endoscopic band ligation (EBL) alone are the main endoscopic hemostatic methods for colonic diverticular bleeding (CDB). We have established a novel method combining EBL and clipping (EBL-C) for the hemostasis of CDB (Endoscopy E-videos); this study evaluated its usefulness. From March 2019 to July 2024, we endoscopically treated 138 patients for CDB at our institution. We retrospectively compared two groups: those treated with EBL (n=24) and those treated with EBL-C (n=56). Risk factors for early rebleeding were also examined in the EBL-C group. The rate of early rebleeding (defined as rebleeding occurring within 30 days) was lower in the EBL-C group than in the EBL group, although this difference was only marginally non-significant (8.9% vs. 25.0%, P=0.0776). The failure of neck formation was the only independent risk factor for rebleeding (adjusted odds ratio [OR] 0.076; 95% confidence interval [CI] 0.015–0.398; P=0.0023). The frequency of neck formation was significantly higher in the EBL-C group (EBL-C: 89.3% vs. EBL: 66.7%, P=0.0235). Undergoing EBL-C was the only independent factor contributing to the successful development of neck formation (adjusted OR 7.01; 95%CI 1.41–34.8; P=0.0095). Previous treatment of the same diverticulum, neck formation failure, and insufficient clipping were risk factors for early rebleeding. Using EBL-C for CDB may be more effective in preventing rebleeding than using EBL alone, as it facilitates better ligation of the target diverticulum. The treatment of diverticula that are hard and difficult to manage with suction remains a challenge.